Anomalous Transport in Velocity Space: Equation and Models - Trigger, S.A. (Відділення фізики і астрономії НАН України, 2010)
The problem of anomalous diffusion in the momentum space is considered on the basis of the appropriate probability transition function (PTF). A new general equation for the description of the diffusion of heavy particles in a gas of light particles is formulated on the basis of the new approach similar to one in the coordinate space. The obtained results allow one to describe the various situations where the probability transition function has a long tail in the momentum space. The effective friction and diffusion coefficients are determined.